Alellopathic effects of some leguminosae and gramineae species on weeds - Medeiros, A.R.M.; Castro, L.A.S.; Lucchesi, A.A. (Anais da Escola Superior de Agricultura Luiz de Queiroz, 1990)
The alellopathic effects produced by five vegetables species: Avena sativa L., Lolium multiflorum Lam., Vicia sp., Medicago sativa L. and Trifolium repens L. were studied as to their effect on weeds. Individual plots were prepared, fertis. A high weed incidence was noted in the plots of Trifolized and sowed according to the usual recomendationlium repens L. and Medicago sativa L.; in the plots of Avena sativa L. and Lolium multiflorum Lam. , few weed specimens were found; the plot of Vicia sp. maintained an intermediate position. Based on the data obtained it is possible to recommend the two grass species as alellopathic plants to cover the soil. Vicia sp. is indicated when besides the reduction of weed plants, organic matter is desired for incorporation.